Multi-degree of freedom joystick for virtual reality simulation. (November 2013) - Head, M. J.; Nelson, C. A.; Siu, K. C.
Abstract A modular control interface and simulated virtual reality environment were designed and created in order to determine how the kinematic architecture of a control interface affects minimally invasive surgery training. A user is able to selectively determine the kinematic configuration of an input device (number, type and location of degrees of freedom) for a specific surgical simulation through the use of modular joints and constraint components. Furthermore, passive locking was designed and implemented through the use of inflated latex tubing around rotational joints in order to allow a user to step away from a simulation without unwanted tool motion. It is believed that these features will facilitate improved simulation of a variety of surgical procedures and, thus, improve surgical skills training.